Age-Dependent Changes in Nrf2/Keap1 and Target Antioxidant Protein Expression Correlate to Lipoxidative Adducts, and Are Modulated by Dietary N-3 LCPUFA in the Hippocampus of Mice - Mario Díaz; Catalina Valdés-Baizabal; Daniel Pereda de Pablo; Raquel Marin (MDPI AG, 2024)
The brain has a high metabolism rate that may generate reactive oxygen and nitrogen species. Consequently, nerve cells require highly efficient antioxidant defenses in order to prevent a condition of deleterious oxidative stress. This is particularly relevant in the hippocampus, a highly complex cerebral area involved in processing superior cognitive functions. Most current evidence points to hippocampal oxidative damage as a causal effect for neurodegenerative disorders, especially Alzheimer's disease. Nuclear factor erythroid-2-related factor 2/Kelch-like ECH-associated protein 1 (Nrf2/Keap1) is a master key for the transcriptional regulation of antioxidant and detoxifying systems. It is ubiquitously expressed in brain areas, mainly supporting glial cells. In the present study, we have analyzed the relationships between Nrf2 and Keap1 isoforms in hippocampal tissue in response to aging and dietary long-chain polyunsaturated fatty acids (LCPUFA) supplementation. The possible involvement of lipoxidative and nitrosative by-products in the dynamics of the Nrf2/Keap1 complex was examined though determination of protein adducts, namely malondialdehyde (MDA), 4-hydroxynonenal (HNE), and 3-nitro-tyrosine (NTyr) under basal conditions. The results were correlated to the expression of target proteins heme-oxygenase-1 (HO-1) and glutathione peroxidase 4 (GPx4), whose expressions are known to be regulated by Nrf2/Keap1 signaling activation. All variables in this study were obtained simultaneously from the same preparations, allowing multivariate approaches. The results demonstrate a complex modification of the protein expression patterns together with the formation of adducts in response to aging and diet supplementation. Both parameters exhibited a strong interaction. Noticeably, LCPUFA supplementation to aged animals restored the Nrf2/Keap1/target protein patterns to the status observed in young animals, therefore driving a "rejuvenation" of hippocampal antioxidant defense.